Seizure as Presenting Symptom of Multisystem Inflammatory Syndrome in Children - Eleonora S. D’Ambrosio; Stefanie Gauguet; Christine Miller; Erin McMahon; Christopher Driscoll; Mugdha Mohanty; Thomas Guggina (Case Reports in Infectious Diseases)
We describe the case of a 13-year-old girl who presented with a new-onset seizure and fever and subsequently developed severe cardiac dysfunction, coronary artery dilation, and shock due to the surprising diagnosis of multisystem inflammatory syndrome in children (MIS-C). Although the clinical entity we now call MIS-C was first mentioned in the medical literature in April 2020, the full picture of this disease process is still evolving. Neurologic involvement has been described in cases with MIS-C; however, seizures are not a typical presenting symptom. Additionally, because children infected with SARS-CoV-2 are often asymptomatic, a documented preceding COVID-19 infection might not be available to raise suspicion of MIS-C early on. Febrile seizures, meningitis, and encephalitis are childhood illnesses that pediatricians are generally familiar with, but associating these clinical pictures with MIS-C is uncommon. Given the possibility of rapid clinical cardiogenic decline, as seen in our patient, a prompt diagnosis and appropriate monitoring and treatment are of utmost importance. This case report aims to raise awareness that new-onset seizures with fevers can be early or the first presenting symptoms in children with MIS-C, and further workup and close monitoring may be required.